Electrochemical determination of eugenol using a three-dimensional molecularly imprinted poly (p-aminothiophenol-co-p-aminobenzoic acids) film modified electrode. (20th August 2016) - Yang, Lite; Zhao, Faqiong; Zeng, Baizhao
Highlights: Eugenol imprinted copolymer based chemical sensor was fabricated. Porous GN-CNTs-IL composite was used to improve chemosensor detectability. The composite film presented good sensitivity and selectivity in sensing eugenol. Abstract: A novel electrochemical sensor for eugenol determination was presented, which was composed of molecularly imprinted poly ( p -aminobenzenethiol-co- p -aminobenzoic acid) and ionic liquid (IL, i.e. 1-aminopropyl-3-methylimidazolium bromide) functionalized graphene-carbon nanotubes composite (GN-CNTs-IL). The porous molecularly imprinted copolymer film was prepared on the GN-CNTs-IL by cyclic voltammetry. The template molecule was eugenol, the supporting electrolyte was 25 mM tetrabutylammonium perchlorate ethanol solution, and the concentration ratio of p -aminothiophenol and p -aminobenzoic acid was 1:3. The 3D porous GN-CNTs-IL composite was synthesized through a simple one-step hydrothermal method. After optimizing the preparation and measurement conditions, the obtained sensor showed a linear response to eugenol in the concentration range of 5.0 × 10 −7 to 2.0 × 10 −5  M, and the limit of detection was 1.0 × 10 −7  M (S/N = 3). The sensor had good selectivity, 100-fold glucose, lactose and sucrose did not affect the detection of 5.0 × 10 −6  M eugenol, while 10-fold analogues (i. e. vanillin, methyl eugenol, paeonol and methyl isoeugenol) had no interference. In addition, it also displayed good reproducibility and practicability, and was successfully applied to detect eugenol in real samples.